The Effect of Problem-Focused Coping Strategy Training on Psychological Symptoms of Mothers of Children with Down Syndrome - Masoume Pourmohamadreza-Tajrishi; Parviz Azadfallah; Sahel Hemmati Garakani; Enayatollah Bakhshi (Tehran University of Medical Sciences, 2015)
Background: Anxiety is one of the most common reactions that parents show while understanding their children's intellectual disability due to Down syndrome. Anxiety leads parents not to develop appropriate relations with their children, subsequently their psychological health are at risk. The present study was aimed to determine the effect of problem-focused coping strategy training on psychological symptoms of mothers with Down child. Methods: This was an experimental study with pretest and posttest design with case and control group. Sixty-four mothers were selected randomly from Iranian Down Syndrome Charity Society. They completed Symptoms Checklist90-Revised (SCL-90-R). They were assigned to experimental and control groups in equal. Experimental group participated in 12 training sessions (once a week; 60 minutes for each session) and received problem-focused coping strategy program, but control group did not. After 12th session, all subjects completed SCL-90-R again. Analysis of covariance was used for analyzing the data. Results: There was a significant difference (P<0.01) between experimental and control group according to psychological symptoms and its components (phobia, depression, paranoid thoughts, psychosis, somatic complaints,  interpersonal sensitivity, obsession-compulsion, anxiety and aggression) after participation in intervention sessions. Conclusion: There was a significant decrease in psychological symptoms, phobia, depression, paranoid thoughts, psychosis, somatic complaints, interpersonal sensitivity, obsession-compulsion, anxiety and aggression of experimental group. Our findings showed that problem-focused coping strategy-training program led to improve family's perception towards the child and subsequently promote of mental health of mothers with Down children.